Reproductive hormonal profile in Eastern Pacific green turtles captured in‐water - Howell, Priscilla (2022)
The Eastern Pacifc green turtle (EPGT) has been diferentiating from the green turtle and is currently considered a separate population. This study determined the values of reproductive hormones and total thyroxine of 56 resident foraging green turtles captured between 2012 and 2014 at Golfo Dulce, Costa Rica. All of them underwent a physical examination and were deemed as healthy individuals. The progesterone values were 0.31–2.723 ng/ml, estradiol 25.54–104.129 pg/ml, testosterone 1.94–228.97 ng/dl, and thyroxine 0.5–0.9 μg/dl. Since our population did not show sexual dimorphism, and the curved cara- pace length sizes did not match previous reports, turtles’ sex was determined based on high testosterone concentrations. Our results showed that 48 males (>3 ng/dl), three females (<2 ng/dl), and fve yet undetermined individuals (2–3 ng/dl) were sampled. The green turtle populations at the Golfo Dulce seem to be formed by subpopulations at diferent stages of their reproductive cycle; among them could be males and females close to mating season, foraging females between seasons and sub-adults in their fnal developing habitat. The sampled population included 3 juveniles (one male and two not defned), 45 sub-adults (40 males, three females and one not determined), 7 adults (all males), and one undetermined individual (not sex determined either). The progesterone results indicated that none of the females were nesting; this might indicate that they nest far from the area. The information provided by this study is extremely valuable in the attempts to determine the health status for conservation programs of EPGT in the area.